“What Is Labour’s Stake?”: Workers and the History of Environmentalism in Alberta - Montrie, Chad (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2024)
Although counterintuitive for many academics and lay people alike, the Canadian environmental movement has long included significant engagement from organized labour. More surprising, perhaps, the most dedicated labour environmentalists came from unions representing workers in the auto, steel, mining, chemical, and oil industries. This was certainly the case in Alberta during the 1970s. There, the Oil, Chemical and Atomic Workers (ocaw) used their outsized influence within the Alberta Federation of Labour (afl) to conjoin growing concern about occupational health and safety with developing awareness about air and water pollution beyond the workplace. Drawing on fonds at the University of Calgary Glenbow Archives, Provincial Archives of Alberta, and Library and Archives Canada, this article chronicles and assesses efforts by ocaw officials within the afl to introduce and sustain a labour environmentalist agenda. It also makes an argument for historians interested in the origins and evolution of the Canadian environmental movement to pay closer attention to organized labour.